MENGHINDAR DARI BIAS: Praktik Triangulasi Dan Kesahihan Riset Kualitatif - Moh. Zamili (LP2M Universitas Ibrahimy, 2015)
A doubtly about the result and process of qualitative research couse vagueness in analysis of measure. As if qualitative research is a â€œgrey methodologyâ€ so the relevances between one fact and another fact, data interconnection, even contruction of phenomenon might be otherwise apper a bias. On that reason, trustworthiness criteria, thick description, and triangulation is the answer toward that doubtly.